PERBEDAAN HASIL BELAJAR SISWA YANG DIAJARKAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DAN MODEL PEMBELAJARAN KONVENSIONAL - Wally, Nilam; Molle, Juliana Selvina; Laamena, Christina Martha (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2020)
This research is motivated by student mathematics learning outcomes on the material two-dimentional figure still low. The learning process is still teacher-centered and there is a lack of good cooperation between students in discussions when the learning process takes place. This research is an experimental study that aims to determine whether there are differences in student learning outcomes taught by cooperative models Think Pair share and learning models The conventional research design used is Nonrandomized Control Group Posttest Design. The population in this study were all eighth grade students of Ambon-Wathan High School with 100 students and the sample in this study was 40 students, selected using purposive sampling. The instrument used in this study was in the form of test questions which consisted of question details for the final test. The analysis used is statistical analysis, which is t-test. Calculation results obtained, namely the value of Sig. (2-tailed) < Î± or 0.026 <0.05 which causes H0 to be rejected and H1 to be accepted. Based on the accepted hypothesis, the results of the study showed that there were differences in the learning outcomes of the experimental class and control class students who were taught with the Cooperative learning model of the Think Pair share type and the conventional learning model on the Material of Blocks and Beams